A five-year financial plan for AB Leisure Exponent, Inc. - Dela Cruz, Maria Joanna P. Gonzalez, Andrea Sophia D. Jose, Prinz Aldwin P. Ortiz, Jane Claire C. Rivera, Christianne Mae C. Tan, Franchesca M. Valentino, Ma. Shekainah Adonica M. 4 0 16; 5
ABSTRACT: This study examines the financial performance and challenges faced by AB Leisure Exponent Inc. (ABLE), a subsidiary of Digiplus Interactive Corp., a leader in the Philippine gaming and leisure industry. The purpose of the research is to evaluate the company's profitability and sustainability, given its reliance on innovative gaming platforms like BingoPlus and its increasing operational costs. Utilizing a quantitative research design, the study analyzed ABLE's financial statements for 2019-2023 using financial ratios, trend analysis, and market assessment to identify key issues affecting its performance. The findings highlight a significant imbalance between revenue growth and rising expenditures, particularly in advertising, promotions, and external services. This reliance on cost-intensive promotional strategies has eroded profitability despite the company's strong market presence and innovative offerings. Furthermore, the study underscores the necessity of digital transformation and revenue diversification to maintain competitiveness in a rapidly evolving industry. Theoretical implications of the research emphasize the importance of cost optimization and strategic resource allocation in driving financial sustainability. Originality lies in its actionable recommendations, specifically the proposed third alternative course of action: reducing overreliance on promotional perks and discounts while strategically diversifying revenue streams. This approach aims to minimize advertising and promotion expenses while enhancing operational efficiency and exploring untapped market segments. Investing in digital platforms and data-driven marketing strategies is recommended to strengthen customer engagement and operational agility. By aligning its operational strategies with industry best practices, ABLE can achieve financial stability, secure its market leadership, and deliver long-term value to stakeholders. Keywords: Financial Performance, Gaming Industry, Cost Optimization, Revenue Diversification, Digital Transformation, Financial Sustainability, Market Competitiveness, Operational Efficiency
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2